2016
DOI: 10.1159/000441665
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E-Major Urinary Metabolite as a Biomarker for Inflammation in Ulcerative Colitis: Prostaglandins Revisited

Abstract: With the development of new therapeutic approaches, the ultimate goal of ulcerative colitis (UC) treatment is not only clinical remission but also mucosal healing. Successful mucosal healing has been associated with a dramatic risk reduction in UC recurrence and colitis-associated cancer development, which are the most critical complications of UC. However, invasive tests such as colonoscopy and biopsy are required to evaluate mucosal healing. Therefore, frequent examinations are unsuitable for UC patients. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Prostaglandin plays a pivotal role in allergic inflammation. Moreover, reducing the level of prostaglandin exerts a protective effect against IBD and may represent a future safe treatment for IBD [44][45][46]. Furthermore, treatment with natural products could attenuate colitis by downregulating the level of prostaglandin.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin plays a pivotal role in allergic inflammation. Moreover, reducing the level of prostaglandin exerts a protective effect against IBD and may represent a future safe treatment for IBD [44][45][46]. Furthermore, treatment with natural products could attenuate colitis by downregulating the level of prostaglandin.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the occurrence of chronic ulcerative colitis is accompanied by the formation of immune complexes and cytokines, which is difficult to treat[ 47 ]. Of these cytokines, IL-8 can lead to chemotaxis of neutrophils, eosinophils, lymphocytes and other cells, and the release of media that can damage endothelial cells and related tissues and organs, leading to inflammation[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abdominal pain was not significantly relieved after treatment in the control group, while abdominal pain was relieved in the experimental group. This suggests that neutrophil chemotactic factors are released through the activation of macrophages in patients with chronic ulcerative colitis, and both macrophages and neutrophils can increase IL-8 secretion, leading to inflammation[ 47 ]. After stellate ganglion block treatment, the inflammatory chemokine IL-8 was reduced in patients in the experimental group, chemotaxis was inhibited, and peripheral blood histamine only slightly increased; thus, reducing inflammation[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] High concentrations of PGE2 in inflammatory sites prevents the absorption of electrolytes including sodium and chloride, which stimulates bowel motility. [ 11 ] Previous reports demonstrated PGE-MUM levels reflected disease activity in patients with UC [ 6 ] and CFIP. [ 12 ] Additionally, impaired uptake of PGE led to high concentrations of PGE-MUM in patients with CEAS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] A previous report showed that PGE-MUM was elevated in patients with active ulcerative colitis (UC) and that the cutoff value for histological UC activity and remission was 17.0 μg/g Cre. [ 6 ] In patients with chronic fibrosing interstitial pneumonia (CFIP), PGE-MUM levels were also significantly higher than in controls. [ 7 ] These results suggest that PGE-MUM is a promising biomarker that might reflect disease activity.…”
Section: Introductionmentioning
confidence: 99%